RNA function and phosphorus use by photosynthetic organisms - Raven, John A. (Frontiers in Plant Science, 2013)
Phosphorus (P) in RNA accounts for half or more of the total non-storage P in oxygenic photolithotrophs grown in either P-replete or P-limiting growth conditions. Since many natural environments are P-limited for photosynthetic primary productivity, and peak phosphorus fertilizer production is forecast for the next few decades, the paper analyses what economies in P allocation to RNA could, in principle, increase P use efficiency of growth (rate of dry matter production per unit organism P). The possibilities of decreasing P allocation to RNA without decreasing growth rate include a more widespread down-regulation of RNA production in P-limited organisms (as in the growth rate hypothesis), optimal allocation of P to RNA spatially among cell compartments and organs, and temporally depending on the stage of growth, and, for exponentially growing organisms with a constant fraction of P in RNA, a constant rate of protein synthesis through the diel cycle. Acting on these suggestions would be technically demanding, and could have unintended consequences for other aspect of metabolism.